Trial by fire? Rulewriters, training, the BLM, and EPA. (3rd July 2019) - Rinfret, Sara; Cook, Jeffrey
ABSTRACT: Individual bureaucrats are ultimately tasked with solving complex problems and are expected to do so cost-effectively. The purpose of this paper is to examine an infrequent perspective of administrative rulemaking – training. Simply put, our goal is to examine original interview data with federal rulewriters in two agencies – the Environmental Protection Agency and the Bureau of Land Management to understand how bureaucrats are trained to carry out rules. This exploratory study suggests the importance of training for the next generation of rulewriters. In particular, we demonstrate existing informal training can be effective, but more mechanisms (e.g. formal training and mentoring) is necessary.